Aggression and body image concerns among anabolic androgenic steroid users, contemplators, and controls in Norway. (January 2015) - Jenssen, Ida Heimly; Johannessen, Kim Berg
Highlights: AAS users and contemplators report higher levels of aggression and body dissatisfaction than nonusers. No differences were found between AAS users and AAS contemplators on levels of aggression or body image concern. Interventions relating to aggression and body image concern may be useful to target at-risk and AAS using adolescents. Abstract: AAS users and contemplators were investigated for differences in aggression and body image concern. Prevalence rates were sought as a secondary aim. 396 male adolescents at Norwegian high schools completed a questionnaire battery during school hours. Prevalence of AAS use showed 4.0%; AAS contemplation showed 5.1%. No significant differences between the AAS users and contemplators were found on levels of aggression and body image concern. AAS users and contemplators reported significantly higher levels of aggression and body image concern compared nonusing controls. AAS contemplators enhance understanding of AAS use by representing psychosocial factors contributing to increased aggression, and AAS use or risk thereof indicative of an aggressive personality profile. Body image concerns for AAS users and contemplators may indicate that AAS use does not diminish body image concern, and that body image concern is a risk factor for AAS use. This is supportive of previous research.